ANALISIS PERBANDINGAN TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC PADA BANK BNI DAN BANK BRI PERIODE 2015 – 2017 - Prastianingsih, Julia Eka; Widarno, Bambang; Harimurti, Fadjar (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The purpose of this study was to analyze the soundness of Bank BNI and Bank BRI in 2015 - 2017. This research uses descriptive research with a quantitative approach, using the RGEC approach (Risk Profile, Good Corporate Governance, Earning, Capital). The results of the assessment through the NPL ratio at BRI Bank were superior with an average value of 5.28% and obtained the title of Healthy, and BNI Bank with an average value of 5.09% obtaining a predicate for Healthy. The results of the assessment through the BRI Bank LDR ratio were superior with an average value of 85.02% with the title of Healthy, and Bank BNI with an average value of 92.11% with the title of Fairly Healthy. The factor of GCG of BRI Bank is very good while BNI Bank has the title of Healthy. Fator Earnings are assessed through ROA and NIM ratios. The results of the assessment through the ROA ratio on Bank BRI obtained an average score of 3.64% and obtained the title of Very Healthy, and Bank BNI obtained an average value of 2.55% with the title Very Healthy. The NIM ratio at Bank BRI with an average value of 10.21% with the title of Very Healthy, and Bank BNI with an average value of 7.56% with the title Very Healthy. The CAR factor in Bank BRI with an average value of 21.88% with the title Very Healthy, at BNI Bank with an average value of 19.46% with the title Very Healthy.